EFEKTIVITAS MEDIA PAPAN FLANEL DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN ANAK USIA DINI - Tuzahra, Rauhdiya; Yulsyofriend, Yulsyofriend; Muryanti, Elise; Wirman, Asdi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Early reading proficiency is a crucial foundation for the advancement of early childhood literacy, necessitating suitable and engaging educational resources. This study seeks to evaluate the efficacy of flannel board media on the early reading skills of children at Bhayangkari 05 Painan Kindergarten. The research employed a quantitative method using a quasi-experimental design. The study population comprised all 41 children at Bhayangkari 05 Painan Kindergarten, with a sample of 20 children selected by purposive selection approaches, including 10 children in the experimental group and 10 children in the control group. The research instrument comprised an oral assessment featuring indicators for identifying starting letters, differentiating vowel and consonant sounds, associating images with words, and demonstrating fluent reading skills. The data analysis employed a normality test, a homogeneity test, and a hypothesis test utilising a t-test via the SPSS 26 software. The findings indicated that flannel board media significantly influenced children's early reading skills, with a significance value of 0.022 (p < 0.05). The experimental group exhibited an average increase from 11.80 to 15.50 (a difference of 3.70), whereas the control group demonstrated a mere gain from 11.20 to 12.50 (a difference of 1.30). Flannel board media, as a visual and tactile resource, has demonstrated efficacy in enhancing early reading skills in children, aligning with the developmental learning features of early infancy.Keywords: Flannel Board Media, Early Reading, Early Childhood, Early Literacy.